Risk Factors of Invasive Fungal Infection in Recipients After Liver Transplantation: A Systematic Review and Meta-Analysis - Liu, Min; Zhu, Zhijun; Sun, Liying (Frontiers in Medicine, 2021)
Objectives: Invasive fungal infection (IFI) remains an important cause of mortality in liver transplantation (LT). The objective of this meta-analysis was to identify the risk factors for IFI after LT. Methods: We searched for relevant studies published up to June 2020 from PubMed, Web of Science, Embase and the Cochrane Library. Odds ratios (ORs) and their corresponding 95% confidence intervals (CIs) were used to identify significant differences in risk factors. Heterogeneity between studies was evaluated by I2 test, and potential publication bias was assessed with Egger’s test. Quality of included studies was evaluated with the Newcastle-Ottawa scale (NOS). Results: Fourteen studies enrolling 4284 recipients were included in the meta-analysis. Reoperation (OR=2.18, 95% CI: 1.61–2.94), post-transplantation dialysis (OR=2.03, 95% CI: 1.52–2.72), bacterial infection (OR=1.81, 95% CI: 1.33–2.46), live donor (OR=1.78, 95% CI: 1.20–2.63), re-transplantation (OR=2.45, 95% CI: 1.54–3.89), and fungal colonization (OR=2.60, 95% CI: 1.99–3.42) were associated with the risk factors of IFI after LT. Conclusions: Despite some risk factors have been identified as significant factors for IFI post-LT, which may inform prevention recommendations, rigorous and well-designed studies with adequate sample sizes should be conducted to solve the limitations to this study.